Psychological Intervention Program to Control Stress in Youth Soccer Players - Olmedilla, Aurelio; Moreno-Fernández, Isabel Mª; Gómez-Espejo, Verónica; Robles-Palazón, Francisco Javier; Verdú, Isidro; Ortega, Enrique (Frontiers in Psychology, 2019)
The influence on the psychological well-being of the players and their sports performance seems to be one of the keys to the current sports practice. The purpose of this study was to determine the effectiveness of a psychological intervention program for stress control in youth soccer players. A total sample of 19 male youth soccer players (age: 16.3 ± 0.99 years; years playing soccer: 10.89 ± 1.56 years) completed the current research. The Psychological Characteristics Questionnaire related to Sports Performance (CPRD) was used to assess stress factors related to sports competition. A program based on Cognitive-Behavioral Therapy was implemented during eight sessions of approximately 50 min each. A pre-post design was used and statistical differences between pre- and post-measures were checked through dependent sample t-tests. The results indicated that the post-test scores were higher than the pre-tests in “Influence of the Evaluation of Performance” and “Mental Skills” factors, which supposes a significant improvement of the stress management related to performance evaluation, as well as the use of psychological resources and techniques. In addition, the post-test scores were also higher in the “Stress Control” factor, although in this case the differences were not statistically significant. Practical indications deriving from the findings of this study can help youth soccer players to manage the stress of competition using a psychological training program.